2013
DOI: 10.1021/ef4008399
|View full text |Cite
|
Sign up to set email alerts
|

Syngas Production by Thermochemical Gasification of Carbonaceous Waste Materials in a 150 kWth Packed-Bed Solar Reactor

Abstract: The solar thermochemical steam-based gasification of carbonaceous materials is investigated using concentrated solar energy as the source of the high-temperature process heat. Vis-à-vis conventional autothermal gasification, the solar-driven process delivers a higher syngas output of higher quality and lower CO2 intensity because no portion of the feedstock is combusted and its energy content is solar upgraded. The operation of a solar gasification pilot plant for a 150 kWth solar-radiative power input was ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(41 citation statements)
references
References 32 publications
1
37
0
2
Order By: Relevance
“…Solar gasification experimental setups using various carbonaceous materials [13,14] showed that carbon dioxide concentration decreased as much as temperature in the solar reactor increased. In the cited studies, CO 2 was found to account for less than 1% at 1600K, while H 2 production was around 40%.…”
Section: Page 3 Of 30mentioning
confidence: 99%
“…Solar gasification experimental setups using various carbonaceous materials [13,14] showed that carbon dioxide concentration decreased as much as temperature in the solar reactor increased. In the cited studies, CO 2 was found to account for less than 1% at 1600K, while H 2 production was around 40%.…”
Section: Page 3 Of 30mentioning
confidence: 99%
“…Prominent solar-driven gasifier designs that have been examined in literature have employed entrained flow [11,16,18], drop tubes [7,8,10], packed beds [15,19,20], and fluidized beds [12,[21][22][23][24][25][26][27][28]. Entrained-flow and drop-tube gasifiers generally have very short residence times while benefiting from enhanced heat and mass transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In comparison, with this reactor concept, the indirectly irradiated packed bed reactor, has been proven to be operationally robust at a scale of 150 kW th and could also feasibly operate in a pressurised environment (although this has not yet been experimentally demonstrated). However, in this system solar heat is transferred to the fuel bed via a SiC emitter plate [14][15][16][17][18][19], which makes the reactor less efficient than the solar vortex reactor where coal particles are directly irradiated [11,12]. Furthermore, because the packed bed reactor relies on solar energy alone to drive thermochemical reactions, it is far more susceptible to solar intermittency.…”
Section: Introductionmentioning
confidence: 99%
“…The indirectly irradiated, packed bed solar gasifier has been proven, at a scale of 150 kW th , to be operationally robust [14][15][16][17][18][19]. Concentrated solar thermal radiation is introduced into this reactor through a compound parabolic concentrator (CPC) at the top to irradiate a SiC-coated metal emitter plate (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation